Why did you do that?: luxury brands surviving economic crisis - Worrell, Jennifer, author (Colorado State University. Libraries, 2017)
The Global Financial Crisis of 2007-2010 shook the world. The luxury sector was previously thought to be impervious to economic decline because of its non-cyclical nature (Som & Blanckaert, 2015). However, research has shown that the luxury market was not immune to economic downturn (Halliburton & Kellner, 2011). Relatively few studies have been done about the luxury market brand management during times of economic crisis (Cavender & Kincade, 2014). This exploratory multiple-case study will seek to uncover how and why luxury fashion brand leaders choose brand management strategies during economic crisis.
318 - Jennifer Worrell
Keywords: luxury; brand management; crisis